Freudig in die Schlacht - Emotionen als Codes für die recta intentio im gerechten Krieg (8.- 10. Jahrhundert) - Foerster, Anne (Emotionen im Krieg - Krieg der Emotionen)

The Swineherd’s Wife who Scolded the King - Foerster, Anne (Women in Early Medieval England)

Eadburh of Wessex - Foerster, Anne (Women in Early Medieval England)

Seaxburh - Foerster, Anne (Women in Early Medieval England)

Struktur und Sonderbauten der Silberbergbaustädte des 16. Jahrhunderts. Zur Korrelation von Städtebau und Montanwesen (Potosí und das Erzgebirge) - Silvestri, Marco (Bergbau und Hausbau)

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (arXiv:2401.02368)
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

Hilfst du mir, so hilfst du dir. Diplomatische Überzeugungsstrategien der Regentin Christine Charlotte von Ostfriesland gegenüber Kaiser Leopold I. im 17. Jahrhundert (erscheint 2024) - Becker, Rieke (Österreichische Zeitschrift für Geschichtswissenschaften. Themenband „New Diplomatic History“)
Keywords: New Diplomatic History; Neue Diplomatiegeschichte

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)

BelgienNet – une plateforme pour l’accès aux langues et cultures de la Belgique - Huybrechts, Yves; Karaca, Resul (Synergies Pays germanophones)

Corrosion behaviour of self-piercing riveted joints with uncoated rivets in high nitrogen steel - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Production Engineering)

Historisches Lernen in einer ‚(Geschichts-)Kultur der Digitalität‘? - Hartung, Olaf (Geschichtskulturen im digitalen Wandel?)

Geschichtskulturen im digitalen Wandel?

Het verhaal van Vlaanderen. Analyse van het mediaformat en het geschiedverhaal - Huybrechts, Yves; Schmitz, Sabine (bmgn — Low Countries Historical Review)

Die Vorgeschichte der „sozialen Medien“. Über die Träume digitaler Vergemeinschaftung und freier Kommunikation - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Sind „soziale Medien“ überhaupt ein Thema für die Geschichtswissenschaft? Ja, denn die längere Geschichte der Digitalisierung, in der die „sozialen Medien“ einzuordnen sind, zählt bereits über 80 Jahre. Konrad Zuse und andere Ingenieure entwickelten seit 1941 die ersten Digitalcomputer, Unternehmer*innen, Wissenschaftler*innen und Staatenlenker*innen setzten diese seit den 1950er Jahren für ihre Zwecke ein, die Zivilgesellschaft adaptierte sie in den darauffolgenden Dekaden – all das prägte die sozio-digitale Landschaft der späteren „sozialen Medien“. Als unmittelbar „nach dem Boom“ etwa um 1970 zahlreiche Industriegesellschaften einen strukturellen Wandel in Wirtschaft, Gesellschaft und Politik durchlebten, war eine Antwort darauf die vermehrte Digitalisierung und Vernetzung. Daraus entwickelte sich die 1990er Jahre als markante Dekade von World Wide Web, Google und Chatdiensten. Die Entwicklung der „sozialen Medien“ ist also unter anderem in eine ökonomische und gesellschaftliche Entwicklung der Aufmerksamkeitsökonomie und in die längeren Veränderungen von Wirtschafts- und Gesellschaftsordnungen der Ausdifferenzierung und partiellen Individualisierung seit den 1960er Jahren einzuordnen. Dadurch lässt sich besser verstehen, welche Prämissen ihnen zugrunde lagen, welche Möglichkeitsräume und Probleme sich daraus ergaben und warum sie die heutige Öffentlichkeit in einer bestimmten Art und Weise dominieren – ohne sie jedoch zu determinieren.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; World Wide Web; Digitalisierung

Alles geht? Die jüngste Geschichte der „sozialen Medien“. Zwischen Wirtschaft und Gemeinschaft - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Twitter ist jetzt X und befindet sich auf dem absteigenden Ast. Auf diesem Ast sitzt Facebook bereits seit längerem. Der Kurzvideodienst Vine, Vorgänger von TikTok, ist Geschichte. Und auch bei Google klingeln die Alarmglocken angesichts der „neuen“ Konkurrenz durch Microsoft und ChatGPT. Umso dringlicher wird also die Historisierung der „sozialen Medien“, das heißt, sie in ihren historischen Kontext einzuordnen und ihren Mythos zu entzaubern. Dabei wartet das Vorhaben mit einer doppelten Herausforderung auf: Erstens, dass es sich bei den Unternehmen der Branche und zweitens auch bei den dort gebildeten Gemeinschaften um recht flüchtige, wandelhaften Gestalten handelt. Scheitern und Wandel ist Teil der „sozialen Medien“ – und sei es nur in der schnellen Abfolge der Moden des „nächsten großen Dings“. Dementsprechend versucht dieser Beitrag mit einem systematischeren Ansatz als dem der gesellschaftlichen Selbstbeschreibung, die Entwicklung des sozio-digitalen Phänomens „soziale Medien“ in dessen Zeitkontext einzuordnen.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; Wirtschaftsgeschichte; Digitalisierung; Twitter; Facebook; Meta

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Decomposing large unitaries into multimode devices of arbitrary size - Arends, Christian; Wolf, Lasse Lennart; Meinecke, Jasmin; Barkhofen, Sonja; Weich, Tobias; Bartley, Tim (Physical Review Research)
Keywords: General Physics and Astronomy

Experimentelle und simulative Analyse der Mischwirkung in Einschneckenextrudern - Schadomsky, Michael

Zwischen Beutesuche und politischen Ambitionen. Die Normannen an Rhein und Maas zwischen 880 und 892 - Kamp, Hermann (Zeitschrift des Aachener Geschichtsvereins)

‚Schelmische‘ Post-DDR-Romane: Ingo Schulzes „Peter Holtz“ und Lea Streisands „Hufeland, Ecke Bötzow“ - Elit, Stefan (‚Topographisches‘ Schreiben: Lea Streisand, Paderborn, Wintersemester 2022/2023)

'Topographisches‘ Schreiben: Lea Streisand. Paderborn Wintersemester 2022/23

‚Topographisches‘ Schreiben. Lea Streisand, Paderborn Wintersemester 2022/23: Die 41. Gastdozentur für Schriftstellerinnen und Schriftsteller. Zur Einführung. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Sich selbst erzählen. Lea Streisands autofiktionales Erzählen. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Scalable quantum detector tomography by high-performance computing - Schapeler, Timon; Schade, Robert; Lass, Michael; Plessl, Christian; Bartley, Tim (arXiv:2404.02844)
At large scales, quantum systems may become advantageous over their classical counterparts at performing certain tasks. Developing tools to analyse these systems at the relevant scales, in a manner consistent with quantum mechanics, is therefore critical to benchmarking performance and characterising their operation. While classical computational approaches cannot perform like-for-like computations of quantum systems beyond a certain scale, classical high-performance computing (HPC) may nevertheless be useful for precisely these characterisation and certification tasks. By developing open-source customised algorithms using high-performance computing, we perform quantum tomography on a megascale quantum photonic detector covering a Hilbert space of $10^6$. This requires finding $10^8$ elements of the matrix corresponding to the positive operator valued measure (POVM), the quantum description of the detector, and is achieved in minutes of computation time. Moreover, by exploiting the structure of the problem, we achieve highly efficient parallel scaling, paving the way for quantum objects up to a system size of $10^{12}$ elements to be reconstructed using this method. In general, this shows that a consistent quantum mechanical description of quantum phenomena is applicable at everyday scales. More concretely, this enables the reconstruction of large-scale quantum sources, processes and detectors used in computation and sampling tasks, which may be necessary to prove their nonclassical character or quantum computational advantage.

Asymptotic behavior of solutions to the extension problem for the fractional Laplacian on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Evolution Equations)
Abstract This work deals with the extension problem for the fractional Laplacian on Riemannian symmetric spaces G / K of noncompact type and of general rank, which gives rise to a family of convolution operators, including the Poisson operator. More precisely, motivated by Euclidean results for the Poisson semigroup, we study the long-time asymptotic behavior of solutions to the extension problem for $$L^1$$ L 1 initial data. In the case of the Laplace–Beltrami operator, we show that if the initial data are bi- K -invariant, then the solution to the extension problem behaves asymptotically as the mass times the fundamental solution, but this convergence may break down in the non-bi- K -invariant case. In the second part, we investigate the long-time asymptotic behavior of the extension problem associated with the so-called distinguished Laplacian on G / K . In this case, we observe phenomena which are similar to the Euclidean setting for the Poisson semigroup, such as $$L^1$$ L 1 asymptotic convergence without the assumption of bi- K -invariance.
Keywords: Mathematics (miscellaneous)

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

“Der Draht ist gut, hält uns ab vom dummen Leben“. Ironisierung als kommunikativer Versuch des Umgangs mit Entwertungs- und Gewalterfahrungen durch jüdische Textproduzenten im Getto Litzmannstadt - Markewitz, Friedrich (Invective Discourse)
Immediately after the National Socialist seizure of power, a comprehen-sive social, legal and ultimately existential exclusion of Jewish people began. The disturbing perception of the break-up of previous understandings of the world was intensified against the background of the acts of annihilation by the National Socialists. Countering this in a communicative form became an often agonizing challenge for Jewish speakers, but also a necessary need. This paper will focus on a communicative phenomenon that has been little researched in linguistics so far: The use of irony to counter experiences of devaluation and violence. By eval-uating ironic utterances in textual communications of the Litzmannstadt ghetto, the criticism of elements of National Socialist ideology will be tentatively made understandable, as well as the experiences of violence within the ghetto.

Haus oder Schule? oder Haus und Schule? Zur kulturell-gesellschaftlichen Bedeutung der historischen Textsorte 'Schulprogramm' hinsichtlich der Konstitution, Festigung wie Abgrenzung des Erziehungssystems im 19. Jahrhundert - Markewitz, Friedrich (Textsorten in Sprach-, Kultur- und Sozialgeschichte)

Ironie - Markewitz, Friedrich
Ironie lässt sich als uneigentliches Kommunikationsmittel beschreiben, mit dem etwas anderes zum Ausdruck gebracht wird, als Sprecher*innen oder Schreiber*innen eigentlich meinen. Dies erfordert eine Differenzierung in Gesagtes und Gemeintes. Doch diese Differenzierung ist längst nicht immer eindeutig und so lebt Ironie von einer interpretatorischen Ambivalenz, ob eine Äußerung wörtlich oder ironisch zu verstehen ist. Aufgrund dieser Ambivalenz und ihrer kulturgeschichtlichen Entwicklung erscheint Ironie als ebenso faszinierendes wie komplexes Sprach-Phänomen. Die vorliegende Einführung gibt aus kulturlinguistischer Perspektive Einblicke in die verschiedenen Möglichkeiten der theoretischen Beschreibung, methodischen Erfassung sowie empirischen Analyse von Ironie. Dabei werden einerseits alltagssprachliche Formen ironischen Kommunizierens in den Blick genommen, andererseits Möglichkeiten des interdisziplinären Anschlusses, um Ironie als linguistisches sowie als kulturgeschichtliches Phänomen zugänglich zu machen.

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

Further information about neural valence-dependent processing of augmented feedback in extensive motor practice: An analysis of frontal theta-band activity - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Religion und Freiheit - Süßmann, Johannes

Realization of high-fidelity unitary operations on up to 64 frequency bins - De, Syamsundar; Ansari, Vahid; Sperling, Jan; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Research)
The ability to apply user-chosen large-scale unitary operations with high fidelity to a quantum state is key to realizing future photonic quantum technologies. Here, we realize the implementation of programmable unitary operations on up to 64 frequency-bin modes. To benchmark the performance of our system, we probe different quantum walk unitary operations, in particular, Grover walks on four-dimensional hypercubes with similarities exceeding 95% and quantum walks with 400 steps on circles and finite lines with similarities of 98%. Our results open a path toward implementing high-quality unitary operations, which can form the basis for applications in complex tasks, such as Gaussian boson sampling. Published by the American Physical Society 2024

Inklusion verstehen - Szenen aus dem Unterricht in interdisziplinärer Reflexion
Die Verankerung von Inklusion als Querschnittsthema lehramtsbezogener Studiengänge fordert zu einer interdisziplinären Verständigung über die Vorstellung inklusiver Unterrichtsgestaltung heraus. Die ForscherInnengruppe der Universität Paderborn wählt hierfür als methodischen Ausgangspunkt Vignetten als verdichtete Fallbeispiele aus der Unterrichtspraxis, die aus verschiedenen fachübergreifenden praxistheoretischen Perspektiven gelesen und so gemeinsam diskutiert werden. In der Linie praxistheoretischer Arbeiten reflektiert das Buch Praktiken im inklusiven Fachunterricht in der Spannung zu den normativen (sonder-)pädagogischen bzw. (fach-)didaktischen Vorannahmen, um aus dieser Reflexion eigenes verantwortetes Handeln zu entwickeln. Die Vignettenbündel laden so zum diskursiven Austausch, zur Kontrastierung oder zum "Einfangen" selbst erlebter Unterrichtspraxen auf dem Weg des Verstehens von Inklusion in Theorie und Praxis ein.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Wirtschafts- und Finanzpolitik als Schlüsselbereiche europäischer Einigung - Schönhärl, Korinna; Leucht, Brigitte (Europäische Einigung zwischen Anspruch und Wirklichkeit. Eine historische Bestandsaufnahme)
Im Gespräch loten Brigitte Leucht und Korinna Schönhärl aus, welche Rolle wirtschafts- und finanzpolitische Überlegungen und Faktoren für den europäischen Einigungsprozess gespielt haben und immer noch spielen.
Keywords: Wirtschaftsgeschichte; Europäische Geschichte; Europäische Einigung; Staatsverschuldung; Moderne griechische Geschichte

Histories of Tax Evasion, Avoidance and Resistance - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea
Tax evasion, tax avoidance and tax resistance are widespread phenomena in political, economic, social and fiscal history from antiquity through medieval, early modern and modern times. Histories of Tax Evasion, Avoidance and Resistance shows how different groups and individuals around the globe have succeeded or failed in not paying their due taxes, whether in kind or in cash, on their properties or on their crops. It analyses how, throughout history, wealthy and poor taxpayers have tried to avoid or reduce their tax burden by negotiating with tax authorities, through practices of legal or illegal tax evasion, by filing lawsuits, seeking armed resistance or by migration, and how state authorities have dealt with such acts of claim making, defiance, open resistance or elusion. It fills an important research gap in tax history, addressing questions of tax morale and fairness, and how social and political inequality was negotiated through taxation. It gives rich insights into the development of citizen-state relationships throughout the course of history. The book comprises case studies from Ancient Athens, Roman Egypt, Medieval Europe, Early Modern Mexico, the Ottoman Empire, Nigeria under British colonial rule, the United Kingdom of the early 20th century, Greece during the Second World War, as well as West Germany, Switzerland, Sweden and the United States in the 20th century, including transnational entanglements in the world of late-modern offshore finance and taxation. The authors are experts in fiscal, economic, financial, legal, social and/or cultural history. The book is intended for students, researchers and scholars of economic and financial history, social and world history and political economy. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Share Alike 4.0 license.
Keywords: Tax History; Financial History

The Ability and Intention of Not Paying Taxes in History. Some Introductory Observations - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea (Histories of Tax Evasion, Avoidance and Resistance)
Jean Bodin's list on how the absolutist monarchical state could raise its revenue ranked taxation only in seventh place. From a modern legal perspective, taxes are compulsory transfers of resources that households and enterprises pay to one or several government bodies without receiving an individual, specific benefit in return. Historians have dealt with not paying taxes in various contexts, such as analysing tax resistance and tax resistance movements in history. Tax law is best understood as an outcome of long-term, often conflictual, negotiations and as an expression of specific political mentalities and ideologies. As a consequence, tax law and sometimes even the tax juridical system have a strongly politicised character. Loopholes in tax legislation that enable or facilitate avoidance or evasion can thus be regarded as a result of the interest-driven politics of parliamentary majorities, as the success of concerted lobby pressure.

How to Create a Taxpaying Spirit. A Transnational Examination of an US American and a Western German Tax Education Film in and after World War II - Schönhärl, Korinna (Histories of Tax Evasion, Avoidance and Resistance)
As a case study, this chapter examines two tax education films that were produced 11 years apart in the USA and Western Germany during and after World War II: “The New Spirit” and “Putzke wants to know”. In contrast to America's most popular cartoon character 11 years earlier, Erwin Putzke is in a terrible mood at the beginning of the short film “Putzke wants to know”. The family father and electrician with a workshop of his own is annoyed and upset by the duty of filling in his tax return, grumbling at his wife and daughter and even at their budgie. The film's tax morale message is conveyed to its audience against the backdrop of a sober post-war reality characterised by allied occupation and the Allies' say in West German tax policies during a period of laborious economic build-up after a lost war.

Bibliotheken des Hellwegraums als Orte frühneuzeitlichen Kulturtransfers. Aufriß und Forschungsprogramm - Süßmann, Johannes (Bücher in Westfalen – Westfalen und ihre Bücher. Festschrift für Hermann-Josef Schmalor zum 70. Geburtstag)

In der freiheit musicirt: Musikpraxis und -erziehung in den Taschenkalendern Kaspars von Fürstenberg - Lauert, Markus (Musiklandschaften zwischen Pader und Rhein. Verflechtung und Pluralisierung entlang des Hellwegs)

Die mündliche Prüfung. Eine Einführung - Matz, Frauke; Rogge, Michael; Rumlich, Dominik

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Immaterielles Kulturerbe in Nordrhein-Westfalen. Zur Bedeutung kultureller Ausdrucksformen - Harnack, Maria (Immaterielles Kulturerbe und regionale Identität – Schützenwesen in Deutschland)

Deutscher Werkbund, Bauhaus, Hochschule für Gestaltung Ulm - Seng, Eva- Maria

Zu »wahrer Glückseligkeit« anleiten. WWU-Gründervater Franz von Fürstenberg wollte vor allem den Fortbestand des Landes sichern – ein Gastbeitrag - Süßmann, Johannes (wissen/leben. Die Zeitung der WWU Münster)

Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Alterungsmechanismen von Haushaltskältegeräten - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Reineke, Michael; Kasper, Tina; Schumacher, Daniel; Vrabec, Jadran; Hüppe, Christian; Stamminger, Rainer; Hölscher, Heike; Stoll, Ragnar; Wagner, Hendrik; et al.
Die für die Berechnung des Energieeffizienzindex von Haushaltskältegeräten benötigten Parameter werden durch Norm-Messungen im Neuzustand der Geräte bestimmt. Aus früheren Untersuchungen ist bekannt, dass durch verschiedene technische Alterungsmechanismen der Energieverbrauch über eine Produktlebensdauer von 18 Jahren um bis zu 33 % zunehmen kann. Ziel des vom BMWi geförderten Projekts ALGE war es, die verschie-denen Ursachen und Einflussgrößen für die Alterung von Haushaltskältegeräten zu ermitteln und eine Alterungs-funktion zu bestimmen, die den zeitlichen Verlauf des zunehmenden Energieverbrauchs beschreibt. In diesem Projekt wurde das Alterungsverhalten von Haushaltskältegeräten durch 100 Normenergieverbrauchs-messungen an 32 real gealterten Geräten untersucht. Aus den gewonnenen Ergebnissen konnte eine Alterungs-funktion bestimmt werden, die den Anstieg des Energieverbrauchs beschreibt. Alle untersuchten Geräte wurden an der Universität Paderborn im Neuzustand vermessen und nach einer Laufzeit von bis zu 21 Jahren erneut geprüft. Bereits nach einem zweijährigen Betrieb konnte ein Mehrverbrauch von bis zu 11 % festgestellt werden. Über die durchschnittliche Produktlebensdauer von Haushaltskältegeräten von ca. 16 Jahren steigert sich der Energieverbrauch um durchschnittlich 27 %. Im Rahmen des Projekts wurden verschiedene Systemkomponenten, wie Isolierung und Verdichter, hinsichtlich ihres Alterungsverhaltens untersucht. Bei dem im Gehäuse als Isolierung verwendeten PUR-Schaum konnte über einen Zeitraum von 31 Monaten ein Anstieg der Wärmeleitfähigkeit von 19,5 W/(m⋅K) auf 24,5 W/(m⋅K) festge-stellt werden. Zur Untersuchung der Alterung der Verdichter wurden zuvor auf einem Kalorimeterteststand ver-messene Verdichter in Geräte eingebaut. Nach einem zweijährigen Betrieb wurden diese Verdichter wieder aus-gebaut und erneut vermessen. Hierbei konnte keine Änderung des COP festgestellt werden. Zusätzlich zu den technischen Parametern wurde der Einfluss des Verbraucherverhaltens analysiert. Hier zeigte sich, dass bis zu 33 % des Gesamtenergieverbrauchs nach einer mehrjährigen Nutzungsdauer verbraucherinduziert sein können.
Keywords: Haushaltskältegeräte; Energieverbrauch; Alterung; Verdichter; PUR-Schaum

Tax Education After WWII: How Spain, the USA, and West Germany Tried to Make Their Citizens Pay Honestly - Schönhärl, Korinna; Düll, Nasrin; Ramírez Lugo , Nadya Melina (Tax Evasion and Tax Havens since the Nineteenth Century)
State education in honest tax payment can be understood as a facet of training in citizenship, i.e. as an attempt by the modern state to standardize the behavior of its citizens and to prevent deviations. Based on this Foucauldian understanding, this exploratory article examines tax education in the United States, Spain, and West Germany from the mid-1940s to the late 1980s. During this period, the USA asserted itself as the champion of tax education and Spain consistently tried to emulate this example, albeit with more modest means and different semantic strategies from as early as the 1960s, when it was still under a autoritarian regime. The FRG, however, completely discontinued its few early attempts at tax education from the mid-1950s onwards. Even during the economic crises and tax scandals of the 1970s, there was no relaunch of the programs. The article locates the reasons for this highly uneven development in the different ideal images of the citizen in the three states.

Musiklandschaften zwischen Rhein und Weser – Einführung - Meine, Sabine; Otto, Arnold; Süßmann, Johannes (Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert)

Aus Erklärvideos lernen - Kulgemeyer, Christoph; Sterzing, Fabian; Hörnlein, Madeleine (Digital Physik unterrichten. Grundlagen, Impulse, Perspektiven)

Bomb the System! Politische Pieces als Partizipationspraktik im öffentlichen Raum - Niemann, Sven (Kunst und Politik. Jahrbuch der Guernica-Gesellschaft. Schwerpunkt: Politisches Graffiti.)

Effect of a controlled lifestyle intervention on medication use and costs: The Healthy Lifestyle Community Program (cohort 2) - Kranz, Ragna-Marie; Kettler, Carmen; Anand, Corinna; Koeder, Christian; Husain, Sarah; Schoch, Nora; Buyken, Anette; Englert, Heike (Nutrition and Health)
Background: Establishing a healthy lifestyle has a great potential to reduce the prevalence of non-communicable diseases (NCDs) and their risk factors. NCDs contribute immensely to the economic costs of the health care system arising from therapy, medication use, and productivity loss. Aim: The aim of this study was to evaluate the effect of the Healthy Lifestyle Community Program (cohort 2; HLCP-2) on medication use and consequently on medication costs for selected NCDs (diabetes, hypertension, and dyslipidemia). Methods: Data stem from a 24-month non-randomised, controlled intervention trial aiming to improve risk factors for NCDs. Participants completed questionnaires at six measurement time points assessing medication use, from which costs were calculated. The following medication groups were included in the analysis as NCD medication: glucose-lowering medications (GLM), antihypertensive drugs (AHD) and lipid-lowering drugs (LLD). Statistical tests for inter- and intra-group comparison and multiple regression analysis were performed. Results: In total, 118 participants (intervention group [IG]: n = 79; control group [CG]: n = 39) were considered. Compared to baseline medication use decreased slightly in the IG and increased in the CG. Costs for NCD medication were significantly lower in the IG than in the CG after 6 ( p = 0.004), 12 ( p = 0.040), 18 ( p = 0.003) and 24 months ( p = 0.008). After multiple regression analysis and adjusting for confounders, change of costs differed significantly between the groups in all final models. Conclusion: The HLCP-2 was able to moderately prevent an increase of medication use and thus reduce costs for medication to treat NCDs with the greatest impact on AHD. Trial registration German Clinical Trials Register DRKS ( www.drks.de ; reference: DRKS00018775).
Keywords: Nutrition and Dietetics; General Medicine; Medicine (miscellaneous)

„Löwenstark in der Schwangerschaft!“ Ressourcenaktivierung und Stressreduktion mit dem Zürcher Ressourcen Modell (ZRM®) – eine unkontrollierte Interventionsstudie - Schneider, Tamara; Weber, Julia; Bauer, Nicola H. (Prävention und Gesundheitsförderung)
Jede Schwangerschaft bringt physische, psychische und soziale Veränderungen mit sich. Diese können zu Stress und ambivalenten Gefühlen bei Schwangeren führen, die einen starken Einfluss auf das Wohlbefinden und die Gesundheit von Mutter und Kind haben. Zur Förderung eines komplikationslosen Verlaufs der Schwangerschaft wird in der Forschungsliteratur die Stärkung der gesundheitlichen Ressourcen gefordert. Das Zürcher Ressourcen Modell (ZRM) ist ein ressourcenaktivierendes Selbstmanagementtraining, welches nach aktuellen Studienergebnissen die Gefühlsregulierung unterstützen und Stress reduzieren kann. Ziel dieser Studie war die erstmalige Wirksamkeitsprüfung des ZRM in der Schwangerschaft. Angenommen wurde, dass durch die Aktivierung der persönlichen Ressourcen der Schwangeren das Stresserleben reduziert und das subjektive Wohlbefinden gesteigert werden kann. Die Konstrukte „Stress“ und „Wohlbefinden“ wurden anhand von fünf psychometrischen Parametern operationalisiert. Durchgeführt wurde eine quasiexperimentelle unkontrollierte 6‑stündige Online-Interventionsstudie mit dem ZRM im Januar 2021 an N = 32 Schwangeren, basierend auf einem Prä-Post-Follow-up-Design. Zur Überprüfung der gebildeten Hypothesen wurden einfaktorielle Varianzanalysen (rmANOVAs) durchgeführt. Die 1-faktoriellen rmANOVAs ergaben, dass die ZRM-Intervention das Stresserleben allgemein und schwangerschaftsspezifisch sowie das Angsterleben signifikant senken konnte. Handlungsorientierung nach Misserfolg und emotionales Wohlbefinden konnten signifikant gesteigert werden. Hinsichtlich der subjektiven Vitalität ließ sich lediglich deskriptiv eine Steigerung der Werte verzeichnen. Die ZRM-Intervention erwies sich als wirksame Methode zur Optimierung der Stressbewältigung und Steigerung des Wohlbefindens während der Schwangerschaft. Es kann zielführend sein, das ZRM-Training als Ergänzung zur üblichen Geburtsvorbereitung einzusetzen. Zukünftige Forschungsarbeiten sollten v. a. die Übertragbarkeit der Ergebnisse unter Einbindung einer Kontrollgruppe sicherstellen.
Keywords: Public Health; Environmental and Occupational Health

Potenziale der Kulturerbe-Konvention von 2003. Beispiele aus der Beratungspraxis der Landesstelle Immaterielles Kulturerbe NRW - Harnack, Maria (Kulturerbe als kulturelle Praxis – Kulturerbe in der Beratungspraxis)

Tagungsbericht: 10/20 Jahre UNESCO-Konvention zum Erhalt des Immateriellen Kulturerbes – Auftaktveranstaltung zum Doppeljubiläum - Leineweber, Jonas

Generation of 100 GHz Periodic Nyquist Pulses using Cascaded Mach-Zehnder Modulators in a Silicon Electronic-Photonic Platform - Kress, Christian; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (Conference on Lasers and Electro-Optics (CLEO) 2023)
A frequency-flexible Nyquist pulse synthesizer is presented with optical pulse bandwidths up to fopt=100 GHz and repetition rates equal to fopt/9, fabricated in an electronic-photonic co-integrated platform utilizing linear on-chip drivers.

Multiprotein Adsorption from Human Serum at Gold and Oxidized Iron Surfaces Studied by Atomic Force Microscopy and Polarization-Modulation Infrared Reflection Absorption Spectroscopy - Huang, Jingyuan; Qiu, Yunshu; Lücke, Felix; Su, Jiangling; Grundmeier, Guido; Keller, Adrian (Molecules)
Multiprotein adsorption from complex body fluids represents a highly important and complicated phenomenon in medicine. In this work, multiprotein adsorption from diluted human serum at gold and oxidized iron surfaces is investigated at different serum concentrations and pH values. Adsorption-induced changes in surface topography and the total amount of adsorbed proteins are quantified by atomic force microscopy (AFM) and polarization-modulation infrared reflection absorption spectroscopy (PM-IRRAS), respectively. For both surfaces, stronger protein adsorption is observed at pH 6 compared to pH 7 and pH 8. PM-IRRAS furthermore provides some qualitative insights into the pH-dependent alterations in the composition of the adsorbed multiprotein films. Changes in the amide II/amide I band area ratio and in particular side-chain IR absorption suggest that the increased adsorption at pH 6 is accompanied by a change in protein film composition. Presumably, this is mostly driven by the adsorption of human serum albumin, which at pH 6 adsorbs more readily and thereby replaces other proteins with lower surface affinities in the resulting multiprotein film.
Keywords: Chemistry (miscellaneous); Analytical Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Molecular Medicine; Drug Discovery; Pharmaceutical Science

My first contact with the Foodsharing Initiative - Vochatzer, Stefanie (Creative Approaches to Climate and Peace Education. An Educationr’s Guide to Using Storytelling and Art)

16 Fragen, 16 Antworten: In unserer Rubrik „Lehren im Leben” stellen wir Menschen vor, die Hochschullehre gestalten. Folge 6: Dr. Nerea Vöing - Vöing, Nerea (Lehren im Leben - Blog der Stiftung Innovation in der Hochschullehre)

»In der Art von Inschriften«. Emblematische Inschriftendichtung als Darstellungsprinzip von Ferdinand von Fürstenbergs Monumenta Paderbornensia (1669 und 1672) - Süßmann, Johannes (Monumenta. Erinnerungsorte zwischen Weser und Lippe. Die Monumenta Paderbornensia des Ferdinand von Fürstenberg)

Das Aufbegehren der Eroberten. Absichten, Formen und Deutungen im europäischen Mittelalter (8. bis 14. Jahrhundert) - Kamp, Hermann (Eroberte im Mittelalter. Umbruchssituationen erleben, bewältigen, gestalten)

Editorial - Schönhärl, Korinna; Schotters, Frederike; Thiemeyer, Guido (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Ver- gangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischen- menschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuch en Gelddis- kurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Internationale Finanzkontrollen: Griechenland unter internationaler Kuratel im 19. und 21. Jahrhundert - Schönhärl, Korinna (Schulden machen: Praktiken der Staatsverschuldung im langen 20. Jahrhundert)
Ob als Effekt staatlicher Hilfspakete, als kontroverses Thema des EU-Haushalts oder als mögliche Ursache der rasant steigenden Inflation – in einer Welt im Krisenmodus ist das Problem der Staatsverschuldung aktuell wie selten zuvor. Wie und von wem aber werden Staatsschulden tatsächlich »gemacht«? Und wie stellt sich dies in der historischen Perspektive dar? Die Essays dieses Bandes machen das abstrakte Phänomen der öffentlichen Verschuldung und die verborgenen Prozesse hinter den Schuldenquoten zugänglich. Prägende Praktiken der Staatsverschuldung verdeutlichen die Beiträge anhand von fünf Kategorien: den beteiligten Akteuren, den konkreten Artefakten, den politischen Debatten, den globalen Relationen sowie der Zeitlichkeit der Verschuldung der öffentlichen Haushalte.
Keywords: Financial History; Public Debt; Economic History

Reden über Geld (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Vergangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischenmenschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuchen Gelddiskurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Improved Hardness Results for the Guided Local Hamiltonian Problem - Gharibian, Sevag; Hayakawa, Ryu; Gall, François Le; Morimae, Tomoyuki (Proceedings of the 50th EATCS International Colloquium on Automata, Languages and Programming (ICALP))
Estimating the ground state energy of a local Hamiltonian is a central problem in quantum chemistry. In order to further investigate its complexity and the potential of quantum algorithms for quantum chemistry, Gharibian and Le Gall (STOC 2022) recently introduced the guided local Hamiltonian problem (GLH), which is a variant of the local Hamiltonian problem where an approximation of a ground state is given as an additional input. Gharibian and Le Gall showed quantum advantage (more precisely, BQP-completeness) for GLH with $6$-local Hamiltonians when the guiding vector has overlap (inverse-polynomially) close to 1/2 with a ground state. In this paper, we optimally improve both the locality and the overlap parameters: we show that this quantum advantage (BQP-completeness) persists even with 2-local Hamiltonians, and even when the guiding vector has overlap (inverse-polynomially) close to 1 with a ground state. Moreover, we show that the quantum advantage also holds for 2-local physically motivated Hamiltonians on a 2D square lattice. This makes a further step towards establishing practical quantum advantage in quantum chemistry.

Tax Morale and the Church: How Catholic Clergies Adapted Norms of Paying Taxes to Secular Institutions (1940s–1950s) - Schönhärl, Korinna (Reassessing the Moral Economy Religion and Economic Ethics from Ancient Greece to the 20th Century)
Paying taxes is a field of economic activity that has always been highly morally charged: the question of who pays how much or can avoid or evade the prescribed payments is always closely related to debate about a fair societal distribution of burdens. In the process of moralisation, therefore, faith communities such as the Catholic Church also repeatedly seized the floor to propagate certain norms. The article examines the contributions of theologians from Spain, the USA and West Germany in the 1940s and 1950s. It concludes that the norms of taxation they propagated differed greatly depending on the institutional and economic frameworks within which they operated. The analysis proves taxation to be a field of economic action and societal dispute where economics and morality are indissolubly interconnected.
Keywords: Tax history; religious history: financial history; catholic church; history of economic thought

Regierende Herrscherwitwen und die Angst vor Fremdherrschaft. Zum Verhältnis von Dynastie und Geschlecht - Foerster, Anne (Regentinnen und andere Stellvertreterfiguren Vom 10. bis zum 15. Jahrhundert)

Die Stimmen der Eroberten bei Ermoldus Nigellus. Eine Mahnung an Ludwig den Frommen und Pippin von Aquitanien - Foerster, Anne (Eroberte im Mittelalter: Umbruchssituationen erleben, bewältigen, gestalten)

Privacy-Preserving Natural Language Processing - Habernal, Ivan; Mireshghallah, Fatemehsadat; Thaine, Patricia; Ghanavati, Sepideh; Feyisetan, Oluwaseyi (Proceedings of the 17th Conference of the European Chapter of the Association for Computational Linguistics: Tutorial Abstracts)

Text-Bild-Bezüge in illustrierten Flugblättern von 1500 bis 1700 - Wille, Manuel (Text und Bild: Relationen und Funktionen in Texten vom 8. bis 18. Jahrhundert : Akten zum internationalen Kongress 17. bis 19. Juni 2021)

An Optimized Third-Harmonic Injection Reduces DC-Link Voltage Ripple in Cascaded H-Bridge Converters up to 50% for all Power Factors - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe))
Star-connected cascaded H-bridge Converters require large DC-link capacitors to buffer the second-order harmonic voltage ripple. First, it is analytically proven that the DC-link voltage ripple is proportional to the apparent converter power and does not depend on the power factor for nominal operation with sinusoidal reference arm voltages and currents. A third-harmonic zero-sequence voltage injection with an optimal amplitude and phase angle transforms the 2nd harmonic to a 4th harmonic DC-link voltage ripple. This reduces the voltage ripple by exactly 50% for all power factors at steady-state at balanced conditions. However, this requires 54% additional modules for unity power factor operation and even 100% for pure reactive power operation to account for the increased reference arm voltages due to the large amplitude of the optimal third-harmonic injection. If not enough modules are available, an adaptive discontinuous PWM is utilized to still minimize the voltage ripple for the given number of modules and power factor. With a very limited number of modules (modulation index is 1.15), the proposed method still reduces the DC-link voltage ripple by 24.4% for unity power factor operation. It requires the same number of modules as the commonly utilized 3rd harmonic injection with 1/6 of the grid voltage amplitude and achieves superior results. Simulations of a 10 kV/1 MVA system confirm the analysis.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Capacitor voltage ripple; Zero sequence voltage; Third harmonic injection

Review on: Christos Tsakas: Post-war Greco-German Relations, 1953-1981. Economic Development, Business Interests and European Integration, Basingstoke 2022. - Schönhärl, Korinna (Sehepunkte)

Medienpädagogische Professionalisierung in der beruflichen Weiterbildung. Eine Studie aus Perspektive der biografischen Medienforschung - Dehmel, Lukas

When Did Europe Become Identified With Christianity? The Revolutionary Origins of an All Too Common Slogan - Süßmann, Johannes (Beyond Binaries. Religious Diversity in Europe)

Al Vostro Servizio - Schulze, Max (Buch Handlung Welt Bücher)
Buch Handlung Welt – in drei Worten − wurde von der Künstlerin Hilka Nordhausen 1976 im Hamburger Karolinenviertel eröffnet. Ein Laden, der Unmengen an Drucken, Heften, Broschüren, Taschenbüchern, Publikationen aus dem Underground, aus Übersee, der Kunst und Esoterik, auch selbstverlegte Bücher, Kataloge und Zines versammelte, die in wirren Stapeln halbhohe Tische bedeckten. Zwischen den überquellenden Bücherregalen fanden Lesungen und Performances statt, Filme und alles mögliche andere wurden projiziert. Fast jeden Monat entstand ein neues Wandbild in den Räumen. Die Buch Handlung Welt war bis 1983 in Hamburg der Ort für selbstorganisiertes künstlerisches Handeln − ein Anschlag auf die Wirklichkeit. Ein Konvolut dieser Bücher und Zeitschriften befindet sich im Nachlass von Hilka Nordhausen. 40 Jahre später stellt sich die Frage: Was bleibt von den Büchern, welchen Zeitgeist transportieren sie? Welche haben auch heute noch Bedeutung? Dieses Buch versammelt eine Reihe von subjektiven und widersprüchlichen Einschätzungen zu diesen Titeln, von jungen und mittelalten Künstler*innen und Wissenschaftler*innen.
Keywords: Buch Handlung Welt; Hilka Nordhausen; Achim Duchow; Martin Kippnberger

Rezension von: Jörg van Norden: Verlust der Vergangenheit. Historische Erkenntnis und Materialität zwischen Wiedererkennen und Befremden, Frankfurt/M.: Wochenschau-Verlag 2022 - Hartung, Olaf (sehepunkte)

Lydia Böttger (Universität Paderborn) rezensiert: Burwitz-Melzer, Eva; Riemer, Claudia; Schmelter, Lars (Hrsg.) (2022): Feedback beim Lehren und Lernen von Fremd- und Zweitsprachen. Arbeitspapiere der 42. Frühjahrs- konferenz zur Erforschung des Fremdsprachenunterrichts. [Giessener Beiträge zur Fremdsprachendidaktik]. Tübingen: Narr Francke Attempto, 245 Seiten. ISBN 978-3- 8233-8569-1 - Böttger, Lydia (www.daz-portal.de)

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Ambivalenzkompetenz? Rückblick auf die Tagung "Katastrophen". Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert am Vortag des russischen Angriffs auf die Ukraine - Schroeter-Wittke, Harald; Breckner, Anne (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert

Kompromisse vor dem Kompromiss: Friedensstiftung im hohen Mittelalter - Kamp, Hermann (Kompromissfindung in der Literatur und Kultur des Mittelalters: Strategien und Narrative zwischen Zweifel, Dissens und Aporie)

Gebaute Heiligung. Wie Stadtumbau und Heiligenverehrung des späten 17. und frühen 18. Jahrhunderts Paderborn in eine heilige Stadt verwandelten - Süßmann, Johannes ((Un)verfügbar – Kulturen des Heiligen)
Nach dem Dreißigjährigen Krieg kam es in Paderborn zu einem Stadtumbau. Unter der Regierung des Fürstbischofs Ferdinand von Fürstenberg (1661–1683) wurden drei neue Kirchen errichtet, eine ältere erhielt eine neue Fassade. Das machte alle vier zu städtebaulichen Dominanten – nicht nur durch Größe und Positionierung, sondern weil sie die Barockfassade in Paderborn einführten und damit die Kirchen in ein neues Verhältnis zum städtischen Raum rückten. Gestaltet als Schaufronten vor bühnenartigen Vorplätzen, trugen die Fassaden dazu bei, die vorher auf die Innenräume beschränkte Heiligenverehrung in den Stadtraum hinaus zu wenden und auch im Alltag vor Augen zu stellen. Zugleich wurde ein neuer Prozessionsweg geschaffen, der die Verehrung aller Kirchenpatrone zusammenführte und zu einer Aufgabe für die gesamte Stadt machte. Über Wallfahrtskapellen bezog man das Umland mit ein. Das gesamte Fürstbistum wurde geheiligt. Der politische Sinn war, es nach den Erschütterungen des Dreißigjährigen Kriegs im Innern neu zu begründen und nach außen sakrosankt zu machen.

Modellierung der Feststoffförderung im Einzug von Nutbuchsenextrudern mit Hilfe von DEM-Simulationen - Brüning, Florian
Bei der Auslegung von Einschnecken-Plastifizierextrudern mit genutetem Einzug sind Simulationen ein gängiges Mittel, um zeit-, ressourcen- und kostenintensive experimentelle Untersuchungen einzusparen. Bestehende mathematisch-physi-kalische Berechnungsmodelle auf Basis analytischer Gleichungen weisen jedoch einige Annahmen und Vereinfachungen auf, die die Qualität der rechnerischen Vorhersage reduzieren können. Diese Arbeit liefert daher einen Beitrag, indem analytische Modelle zur Berechnung des Druck-Durchsatz-Verhaltens und der Antriebsleistung in genuteten Einzugszonen mithilfe von numerischen Simulatio-nen basierend auf der Diskrete-Elemente-Methode (DEM) überprüft werden. Es wird gezeigt, dass die Annahme eines gegendruckunabhängigen Durchsatzver-haltens sowie die Unterscheidung in form- und reibschlüssige Förderfälle ge-rechtfertigt ist. Die Annahme einer Blockströmung ist oft nicht gerechtfertigt, auch wenn dies nicht notwendigerweise zu Abweichungen in der Durchsatzberech-nung führt. Für die analytische Durchsatz- und Leistungsberechnung werden re-gressionsbasierte Korrekturfaktoren eingeführt, die die Vorhersagegenauigkeit steigern. Weiterführende Untersuchungen zeigen, unter welchen Bedingungen und mit welchen Maßnahmen sich der Durchsatz von genuteten Einzugszonen steigern lässt. Schließlich wird eine Methode zur Kalibrierung von DEM-Simula-tionen vorgestellt, mit welcher sich die Abbildungsgenauigkeit des tribologischen Verhaltens des Schüttguts erhöhen lässt.

Sprachlichkeit des Geschichtslernens. Fachliche Grundlagen, Sprachgebrauch und Ansätze fachintegrierter Spracharbeit - Hartung, Olaf (Beiträge zur Lehrerinnen- und Lehrerbildung)

„Fotos, die jede:r kennt“ Eine empirische Untersuchung historischer Kenntnisse anhand von Bildikonen bei Studierenden des Lehramts Geschichte - Fastlabend-Vargas, Daniel; Meyer-Hamme, Johannes (Geschichtsdidaktisch intervenieren. Beiträge zur Forschungswerkstatt „Geschichtsdidaktik Empirisch“ 2020)

Anchoring and electro-optic switching of liquid crystals on nano-structured surfaces fabricated by two-photon based nano-printing - Zhang, Bingru; Plidschun, Malte; Schmidt, Markus A.; Kitzerow, Heinz-Siegfried (Optical Materials Express)
The alignment of liquid crystals on surfaces plays a central role in optimizing their performances. In this work, a cutting-edge nano-lithography-based method to control the local orientation of a thermotropic liquid crystal is applied to easily available commercial standard materials and evaluated. Parallel nanogrooves on a substrate, created through 3D nanoprinting in a negative-tone photoresin optimized for two-photon polymerization are used for this purpose. Azimuthal anchoring energies of the order from 10 −6 J/m 2 to 10 −5 J/m 2 are found, depending on the spacing, width and depth of the grooves. In part, these values are larger than those reported previously for another photopolymer. Both uniform alignment and spatial patterns of different alignment directions can be realized. Electro-optic studies confirm the suitability of the method for electrically addressable photonic applications and indicate strong polar anchoring.
Keywords: Electronic; Optical and Magnetic Materials

"Belgische Literatur in deutscher Übersetzung. Ein Interview mit der Übersetzungswissenschaftlerin Anja Van de Pol-Tegge" (PODCAST) - Huybrechts, Yves

"Vlaanderen Feest! - Der flämische Feiertag 2023" (VIDEO) - Huybrechts, Yves

Österreich zwischen Vorbildfunktion und Eigeninteresse. Der Fall Jever, 1737-1739 - Huybrechts, Yves (Konkurrenzen in der Frühen Neuzeit: Aufeinandertreffen - Übereinstimmung - Rivalität)

Riegel, Ulrich / Zimmermann, Mirjam (2022). Evaluation des konfessionell-kooperativen Religionsunterrichts in Nordrhein-Westfalen. Stuttgart: Kohlhammer. ISBN 978-3-17-043134-8. 333 Seiten. - Hüster, Jonas Maximilian (Religionspädagogische Beiträge)
Keywords: Religious studies; Education

Impulse 6. Texte und Bilder zur Kunstvermittlung: ABHÄNGEN. Ein interdisziplinäres Projekt zur documenta fifteen (2022).

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 6: Taschennotizbücher1931–32. Anmerkungen, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2022, xiii, 192 S. - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 07469681)

Untersuchung des Einflusses von Relativverschiebungen während der Aushärtung auf die mechanischen Eigenschaften von Klebverbindungen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)

Experimentelle Untersuchung des Ermüdungsverhaltens von strukturellen Klebverbindungen und Berechnung der Lebensdauer unter Berücksichtigung der Spannungsanisotropie - Tews, Karina; Çavdar, Serkan; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)

Untersuchung der Dichtheitseigenschaften hybridgefügter Mischbauverbindungen für den Einsatz in Batterieghäusen für Elektrofahrzeuge - Schmolke, Tobias; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)